APPLICATION DELIVERY OF GOODS AND DOCUMENTS PT BYMATRANS USING VISUAL BASIC 6.0 - Ahmad Fauzi; Melani Dewi Lusita (Jurnal Sistem Informasi, 2006)
This writing contains about administrative problems in delivery of documents or goods atPT BYMATRANS by using visual basic. The author proposes an application to facilitatethe process of shipping an item or document. With the aim to make it easier to obta ininformation about the status of delivery of goods or documents.In this application can save the document or item of data, address, purpose and durationof delivery.